2022
DOI: 10.3389/fgene.2022.823238
|View full text |Cite
|
Sign up to set email alerts
|

Role of Circular RNAs in the Regulation of Immune Cells in Response to Cancer Therapies

Abstract: Circular RNAs (CircRNAs) are a class of small endogenous noncoding RNA that are formed by means of either the spliceosome or lariat-type splicing. CircRNAs have multiple regulatory functions and have been detected in different cell types, like normal, tumor and immune cells. CircRNAs have been suggested to regulate T cell functions in response to cancer. CircRNAs can enter into T cells and promote the expression of molecules that either trigger antitumoral responses or promote suppression and the consequent ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…Since miRNAs’ expression information is absent from our dataset, our conclusions cannot include the direct association with the miRNAs. In line with several previous reports that have highlighted the importance of immune function in the process of melanoma metastasis and ICB response [ 52 , 53 , 54 , 55 ], our results show a profound influence of the dysregulation of these non-coding RNAS (ncRNAs) on the activation or inhibition of key anti-tumor immunological processes, such as the Th1, natural-killer cell-signaling, T-cell receptor signaling or the PD-1–PD-L1 cancer immunotherapy pathways. Interestingly, the expression perturbation of the responders was associated with an increasing expression of PD-1 and PD-L1 (CD274).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Since miRNAs’ expression information is absent from our dataset, our conclusions cannot include the direct association with the miRNAs. In line with several previous reports that have highlighted the importance of immune function in the process of melanoma metastasis and ICB response [ 52 , 53 , 54 , 55 ], our results show a profound influence of the dysregulation of these non-coding RNAS (ncRNAs) on the activation or inhibition of key anti-tumor immunological processes, such as the Th1, natural-killer cell-signaling, T-cell receptor signaling or the PD-1–PD-L1 cancer immunotherapy pathways. Interestingly, the expression perturbation of the responders was associated with an increasing expression of PD-1 and PD-L1 (CD274).…”
Section: Discussionsupporting
confidence: 92%
“…Some lines of evidence indicate that tumor cells can modify the TIME by recruiting immunosuppressive cells, and both circRNAs and lncRNAs are tools that tumor cells can use via extravesicular particles to obtain a favorable TIME, consequently leading to treatment failure. Interestingly, previous reports, regarding both hepatocellular carcinoma and pancreatic cancer, associated specific circRNAs with the response to targeted therapy and linked them to natural killer cell dysregulation [ 54 ]. With IPA analyses, we can precisely predict functional regulatory networks from gene expression data and assign a significance score to each network based on how well it fits the database’s set of focus genes [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some lines of evidence indicate that tumor cells can modify TIME by recruiting immunosuppressive cells and both circRNA and lncRNA are tools that tumor cells can use, via extravesicular particles, to get favorable TIME and in consequence leading to a treatment failure. Interestingly, previous reports, both in hepatocellular carcinoma and pancreatic cancer, associate specific cirRNA with response to targeted therapy and linked to NK cell dysregulation [69].…”
Section: Discussionmentioning
confidence: 99%
“…CircRNAs are demonstrated to function as miRNA sponges that regulate the downstream target genes. Several circRNAs have been linked to anti-tumor immune regulation through interactions with miRNAs [ 26 , 27 , 31 ]. Zhang et al [ 32 ] demonstrated that hsa_circ_0020397 could upregulate the expression of PD-L1 by binding to miR-138 in colorectal cells, thus contributing to a tumor’s escape from immune responses.…”
Section: Discussionmentioning
confidence: 99%